2020
DOI: 10.1039/d0ra05926a
|View full text |Cite
|
Sign up to set email alerts
|

Two 3D Mn-based coordination polymers: synthesis, structure and magnetocaloric effect

Abstract: Two 3D coordination polymers (MnII6 and MnII12MnIII6) were synthesized. Magnetic studies revealed that they are potential magnetic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…During the synthesis, the growth of crystals was influenced by a number of factors, such as temperature, pH value, duration, starting concentrations of reactants, etc. 31,32 In the synthesis of compounds 1 and 2, the reaction temperature is a significant factor. Compound 1 was obtained at 160 °C, which was different from compound 2 at 140 °C.…”
Section: Synthesismentioning
confidence: 99%
“…During the synthesis, the growth of crystals was influenced by a number of factors, such as temperature, pH value, duration, starting concentrations of reactants, etc. 31,32 In the synthesis of compounds 1 and 2, the reaction temperature is a significant factor. Compound 1 was obtained at 160 °C, which was different from compound 2 at 140 °C.…”
Section: Synthesismentioning
confidence: 99%
“…In recent decades, substantial theoretical and experimental endeavors have been focused on the chemistry of metal–organic frameworks (MOF) due to their captivating structural multiformities and excellent properties. And, metal–organic frameworks based on lanthanide-transition (4f–3d) ions exhibit extraordinary physical as well as chemical properties, particularly in magnetism and photoluminescence. As a result, a large amount of MOFs based on 4f–3d ions have been further explored, for instance, [Ln–Cu], [Ln–Cr], [Ln–Co], [Ln–Ni], and [Ln–Mn]. , In comparison with the well-developed cluster chemistry of metal–organic frameworks based on 4f–3d ions, the chemistry of MOFs based on 4f–3p ions has not been fully explored so far. Aluminum is the most adequate metal in the earth’s crust and is extensively employed in printing fabric, water treatment, catalysis, and optics. It is reported that aluminum also possesses the ability of high luminescence efficiency, making it a suitable material for plasma antennas .…”
Section: Introductionmentioning
confidence: 99%
“…Persistent investigation on the synthetic methods demonstrates suitable ligand and anionic templates are the significant conditions to obtain giant 3d-4f nanoclusters. With regard to the ligand-controlled hydrolytic method, according to hard–soft acid–base theory, 3d metal ions are inclined to coordinate with soft atoms (such as S and N), while the 4f metal ions tend to bond with hard atoms (such as O and F). , At the same time, the organic ligands containing hard and soft atoms are beneficial to establish giant 3d-4f clusters. For instance, iminodiacetic acid (H 2 IDA) with [N, O, O] donor sites has been widely utilized to construct an extremely diverse family of 3d-4f metal clusters. , Herein, the organic ligand H 2 DTA with multifunctional coordination sites [S, O, O] and a similar structure with H 2 IDA (as depicted in Figure ) is expected to assemble novel high-nuclearity 3d-4f clusters.…”
Section: Introductionmentioning
confidence: 99%